The geography of the effectiveness and consequences of Covid-19 measures: Global evidence - Simplice Asongu; Samba Diop; Joseph Nnanna (African Governance and Development Institute (AGDI), 2020)
This study has: (i) analysed the economic impact of the Covid-19 pandemic, (ii) evaluated the effectiveness and relevance of different measures against the pandemic and (iii) examined nexuses between the corresponding measures and economic outcomes. The study uses a sample of 186 countries divided into four main regions, notably: Asia-Pacific and the Middle East, Europe, Africa and America. 34 preventing and mitigating measures against the Covid19 pandemic are classified into five main categories: lockdown, movement restrictions, governance and economic, social distancing, and public health measures. The empirical evidence is based on comparative difference in means tests and correlation analyses. The findings show how the effectiveness and consequences of the Covid-19 measures are different across regions. In adopting the relevant policies to fight the ongoing pandemic, the comparative insights from the findings in the study are worthwhile. Inter alia: (i) from a holistic perspective, only European countries have favourably benefited from the Covid-19 measures; (ii) lockdown measures at the global level have not been significant in reducing the pandemic; (iii) the restriction of movement measure has been relevant in curbing the spread in the American continent; (iv) social distancing has been productive in Europe and counterproductive in Africa; (v) governance and economic measures have exclusively been relevant in Europe and (vi) overall public health measures have not had the desired outcomes in flattening the infection curve probably because most of the underlying measures are awareness decisions or oriented toward people already infected.
Keywords: E10; E12; E20; E23; I10; I18; 330; Novel Coronavirus; Social Distance; Macroeconomics effects